A future of authoritarian citizens? Explaining why Spanish youth are losing faith in democracy - Lorente, Javier; Jiménez-Bravo, Irene (Frontiers in Political Science, 2025)
This article examines why Spanish young people support democracy to a lesser extent than younger generations decades ago: while youth in previous decades showed stronger democratic commitment, the eventual support an authoritarian regime is increasing among today’s youth. Building on a theoretical discussion, we propose three hypotheses to explain why levels of diffuse democratic support is decreasing among Spanish young people: (1) political ideology, since young people place themselves on the right side of the left-right division to a larger extent and this might affect their democratic support; (2) the influence of radical right parties, since new radical parties, as VOX, are spreading discourses that are mainly critical towards democracy and defend past authoritarian experiences; and, finally, (3) the role of social media where these radical discourses that challenge democracy. Analysing survey data from the Spanish Centre for Sociological Research, our results highlight the relevance of young people who place themselves at the centre of the ideological spectrum in understanding this decline in young people’s levels of democratic support. We also explore the presence of a gender gap in democratic attitudes—given its relevance in other contemporary attitudinal and behavioural shifts affecting young people in many Western countries—but find no evidence of such a gap.